(untitled) (Medical Forum Monthly, 2026)
Objective: To investigate the association between the SLC2A4 rs5435 (T>C) single nucleotide polymorphism and glycemic response to exogenous insulin in Iraqi patients with type 1 diabetes mellitus. Study Design: A case–control studyPlace and Duration of Study: This study was conducted at the Department of Pharmacology and Toxicology, Faculty of Pharmacy, Kerbala University, Iraq from 1st December 2023 to 31st December 2024. Methods: This study was conducted involving 100 patients with type 1 diabetes and 30 healthy controls assessed fasting serum glucose and HbA1c levels and genotyped the SLC2A4 rs5435 (T>C) polymorphism using allele- specific polymerase chain reaction. Genotype and allele frequencies were compared between groups and analyzed for associations with glycemic parameters. Results: Among patients with type 1 diabetes, genotype frequencies were 89% for homozygous wild-type (TT), 6% for heterozygous mutant (TC), and 5% for homozygous mutant (CC). In the healthy control group, the corresponding frequencies were 90% (TT), 6.6% (TC), and 3.3% (CC). The SLC2A4 rs5435 (T>C) polymorphism showed no significant differences in genotype or allele distribution between patients and controls and was notassociated with FSG or HbA1c levels, indicating it does not affect response to exogenous insulin therapy. Conclusion: The SLC2A4 rs5435 (T>C) polymorphism does not affect glycemic control or response to exogenous insulin in Iraqi type 1 diabetes patients, though larger multicenter studies are needed to confirm these results and investigate genetic factors influencing insulin responsiveness.